PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Rychy Tri Kusumardana; Kartika Hendra Titisari, Dimas Ilham Nur Rois (PROSIDING, 2022)
Financial performance is a work achievement that has been achieved by the company within a certain period of time and is included in the financial statements of the company concerned. The financial reporting approach uses accounting numbers in financial statements to assess financial performance. Several financial ratios are used as instruments to measure company performance based on financial reporting approaches, including ROA. ROA (Return on Asset) is a measure of a manager's ability to manage assets used to generate profits. This study aims to determine the effect of institutional ownership, managerial ownership, and company size on financial performance. This research was conducted by analyzing transportation service companies listed on the IDX for the 2018-2021 period. Data analysis from this study used descriptive analysis test, classic assumption test, and multiple linear regression test using the SPSS 25 program. The results of this study indicate that corporate managerial ownership has a positive effect on financial performance in transportation service companies listed on the IDX. And institutional ownership and firm size have no effect on financial performance. Keywords: Managerial Ownership, Institutional ownership and Company Size of Transportation Service Companies Listed on the IDX.